ВПЛИВ ВІЙНИ НА ІНВЕСТИЦІЙНИЙ КЛІМАТ УКРАЇНИ: ОЦІНКА РИЗИКІВ ТА ПЕРСПЕКТИВ ДЛЯ ІНОЗЕМНИХ ІНВЕСТОРІВ - Panchenko, Volodymyr (Zhytomyr Ivan Franko State University, 2024)
The article is devoted to a comprehensive analysis of the impact of the Russian-Ukrainian war on the investment climate in Ukraine. Based on current statistical data and expert assessments, the main risks for foreign investors caused by military actions on the country's territory are identified. Among them are: large-scale destruction of critical infrastructure, disruption of established logistics chains, a rapid decline in the purchasing power of the population, as well as a high level of uncertainty regarding the further course and duration of the armed conflict. At the same time, the author considers the potential prospects for restoring the investment attractiveness of Ukraine in the conditions of post-war reconstruction. Special emphasis is placed on forecasting the likely dynamics and sectoral structure of foreign investment in the Ukrainian economy starting from 2025, based on the assumption of the completion of the active phase of hostilities. Based on the identified competitive advantages of Ukraine, a set of measures is proposed to improve the national investment environment in the medium and long term. They include ensuring macroeconomic stability, carrying out structural reforms of the regulatory and judicial systems, strengthening the institutional protection of investors' rights, as well as attracting large-scale financial and technical assistance from international partners. At the same time, the author emphasizes the critical importance of forming a holistic strategic vision for the development of Ukraine as a competitive and investment-attractive state in the long-term horizon, which requires the implementation of a targeted policy to stimulate innovation, build modern infrastructure and integrate into global value chains. The article also analyzes the experience of other countries that have suffered significant economic losses due to military conflicts, and highlights the most effective strategies for restoring investment attractiveness in post-war reconstruction. In particular, successful examples of attracting foreign investment in the countries of the Balkan region and Southeast Asia, which managed to quickly overcome the consequences of armed confrontations and ensure sustainable economic growth, are considered. Based on this experience, the author proposes to adapt best practices to Ukrainian realities, taking into account the specifics of the national institutional environment and geopolitical context. Special attention is paid to the role of international financial institutions, in particular the International Monetary Fund, the World Bank, and the European Bank for Reconstruction and Development, in supporting investment processes in Ukraine in the context of post-war recovery. The importance of aligning their financial and technical assistance programs with national development priorities and ensuring effective coordination of efforts of all stakeholders is emphasized. In summary, the author concludes that restoring the investment attractiveness of Ukraine in the conditions of post-war reconstruction will require a comprehensive approach that combines urgent measures to overcome the devastating consequences of the war with strategic initiatives aimed at ensuring the long-term competitiveness of the national economy. Only under such conditions will Ukraine be able to fully realize its investment potential and become an attractive destination for international capital in the post-war world.